2021
DOI: 10.3390/ijerph18147613
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tooth Scaling with Acute Myocardial Infarction and Analysis of the Corresponding Medical Expenditure: A Nationwide Population-Based Study

Abstract: Accumulating evidence has shown a significant correlation between periodontal diseases and systemic diseases. In this study, we investigated the association between the frequency of tooth scaling and acute myocardial infarction (AMI). Here, a group of 7164 participants who underwent tooth scaling was compared with another group of 7164 participants without tooth scaling through propensity score matching to assess AMI risk by Cox’s proportional hazard regression. The results show that the hazard ratio of AMI fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, a population-based observational study of 247,696 Koreans reported a 14% lower risk of CVD events in individuals with regular dental visits for professional cleaning [ 75 ]. Moreover, in a nationwide study in Taiwan, the incidence rate of acute myocardial infarction was 3.5% in 7164 participants who did not receive dental scaling, almost twice as high as in the matched control group (1.9%) who received regular scaling [ 76 ]. Finally, several systematic reviews agreed that despite evidence of beneficial effects of periodontal treatment on surrogate measures of CVD, there is a lack of adequate randomised controlled trials focusing on hard CVD endpoints to reasonably support or refute preventive effects [ 47 , 70 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a population-based observational study of 247,696 Koreans reported a 14% lower risk of CVD events in individuals with regular dental visits for professional cleaning [ 75 ]. Moreover, in a nationwide study in Taiwan, the incidence rate of acute myocardial infarction was 3.5% in 7164 participants who did not receive dental scaling, almost twice as high as in the matched control group (1.9%) who received regular scaling [ 76 ]. Finally, several systematic reviews agreed that despite evidence of beneficial effects of periodontal treatment on surrogate measures of CVD, there is a lack of adequate randomised controlled trials focusing on hard CVD endpoints to reasonably support or refute preventive effects [ 47 , 70 , 77 ].…”
Section: Discussionmentioning
confidence: 99%